FEATURES OF PLANNING OF HEARING DEVICES ON AN INTEGRAL ELEMENT BASE - Новосядлий, Степан Петрович; Мельник, Любомир Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The basic setting of hearing device (HD) consists in transformation of signal which turns out a sound information generator thus, that this signal could be perceived by a man with the defective hearing, with enough high level auditory feeling. Greater part of people use HD for listening of linguistic signals. In the row of cases HD finds the application in a role of mean of reduce of the bad feelings from a ear noise. Transformations of acoustic signal, that HD is carried out can carry a different character. There is this strengthening of sounds in simplest case. In many practical case of strengthening can be accompanied by low or high-frequency filtration, set limitation of dynamic range of amplifying signal. Exist HD with nonlinear transformation of amplitude frequency spectrum of entrance signal by antinoise treatment of mixture signal-noise, by the simultaneous signal processing in a few frequency ranges. For high-quality HD stability of frequency spectrum, size and stability of tension of feed (powers of consumption) and minimum sizes is important. Given questions and lie in the basis of the given article, the features of the construct scheme planning of HD on an integral element base are examined in which.